ISLAMIC STUDIES TECHNIQUE THROUGH PLAYING, STORY TELLING AND SINGING METHOD FOR KIDS IN LAMBIRAH VILLAGE ACEH BESAR - Meutia Zahara; Nazariah Nazariah; Muhammad Yani; Restu Andrian (ABDIMU: Jurnal Pengabdian Muhammadiyah, 2021)
This community service program aims to teach the Islamic studies to the children with more interesting techniques, so that the children will have more understanding to the material given, this program conducted in Lambirah Village. One of well-known techniques that mostly apply is Playing, Singing and Telling method. This program conducted with some stages; providing the materials to the children, followed by some trainings dan discussion with the audience. The results obtained that this method was successfully attracted the audience or participants attention.Key words: Lambirah, Islamic Studies, BCM Method